Oil Palm (Elaeis guineensis) Responses to Indigenous Mycorrhizae and Cow Manure in Ultisol - Kartika, Elis; Duaja, Made Deviani; Gusniwati, Gusniwati (Universitas Muhammadiyah Yogyakarta, 2019)
The experiment was conducted to examine the effects of indigenous mycorrhizae inoculation and cow manure doses on the growth and yield of oil palm (Elaeis guineensis) at production stages I. It was conducted at farmer plantation in Semabu Village Tebo Regency located at -1.473543, 102484062. This research was arranged in a randomized block design consisting of two factors. The first factor is inoculation of mycorrhizae isolates comprising two levels, i.e. without and with inoculation, and the second factor is the dose of cow manure comprising five levels, i.e. without cow manure, 25%, 50%, 75%, and 100% of the recommended dose of cow manure at Production Stages I (30 kg plant-1). The variables observed were plants girth, leaf midrib, number of bunches per plant, weight per bunch, weight of fresh fruit bunches per plant, and root infection. The results showed that there was interaction effect between inoculation of mycorrhizae and cow manure doses. The inoculation of mycorrhizae and cow manure at a dose of 50% of the recommended dose were able to increase oil palm growth and yield.